Studi Literatur Hubungan Disiplin Kerja dengan Kinerja Karyawan - Permana, Sajim Aji; Solehudin, Solehudin (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Developing technology requires human resources, especially in a company to develop as well. So that employees are obliged to demonstrate good performance, one of them is work discipline. Discipline is an attitude of willingness and willingness to restrain oneself and comply with the surrounding standards and regulations. Employees with work discipline can achieve organizational goals. Work discipline influences the performance of employees in an organization. Performance is the degree to which an activity is capable of achieving a set quantity and quality target. Thus, this study was done to investigate the impact of workplace discipline on employee performance. The research was conducted utilizing qualitative methodologies in the form of multiple relevant literature analyses. The results of this study's literature review indicate that work discipline has a considerably favorable effect on employee performance inside an organization—improved work discipline for employees, resulting in increased employee performance or output. A high level of work discipline can increase company productivity. Keywords: work discipline, employee performance, company